Diagnosis and management of residual atrial septal defect after surgical failure: A case series - Satyavan Sharma; Akash Bhupesh Shah; Shankar Y. Machigar; Rajendra Umbarkar (Annals of Pediatric Cardiology)
Residual defect after surgical closure of atrial septal defect is extremely uncommon. This communication reports four cases encountered in a tertiary care center during the last three decades. Clinical diagnosis was challenging, and the diverse presentations included acute ischemic stroke, cyanosis, and right ventricular volume overload. The morphology of the residual defects was complex, and multimodality imaging (transesophageal echocardiography, peripheral venous contrast studies, computed tomography, and balloon occlusion) enabled accurate recognition. Percutaneous device closure was feasible in one but required repeat surgery owing to unfavorable anatomy in the others. The communication focuses on difficulties in diagnosis and management.